Present status of naturally occurring seaweed flora and their utilization in Bangladesh ... : الوضع الحالي لنباتات الأعشاب البحرية التي تحدث بشكل طبيعي واستخدامها في بنغلاديش ... - Md Shirajul Islam Sarkar; Md Kamal; Muhammad Mehedi Hasan; Md. Ismail Hossain (OpenAlex, 2016)
A survey was conducted to know the present status of naturally occurring seaweed flora and their utilization in Bangladesh by interviews of scientific officers of MFTS (Marine Fisheries and Technology Station, Bangladesh Fisheries Research Institute, Cox's Bazar), NGO officials associated with seaweed research project, local seaweed food products manufacturer, seaweed collectors and Mog or Rakhyine tribal community of Cox's Bazar and St. Martin Island. Lack of knowledge on availability, distribution, seasonal variation, utilization status is causing impediment on utilization (e.g. seaweeds as human food, hydrocolloids, animal feed, fertilizer, cosmetic products, etc.) of available seaweeds naturally occurring in Bangladesh. Seaweeds are available along the whole Bangladeshi coast, mostly in St. Martin Island, Cox's Bazar and Sundarbans Mangrove forest. Total 193seaweed species including 19 commercially important species, belonging to 94 genera are found. Approximately, 5,000 metric ton of seaweed biomass is ... : تم إجراء مسح لمعرفة الوضع الحالي لنباتات الأعشاب البحرية التي تحدث بشكل طبيعي واستخدامها في بنغلاديش من خلال مقابلات مع المسؤولين العلميين في MFTS (محطة مصايد الأسماك البحرية والتكنولوجيا، معهد بنغلاديش لبحوث مصايد الأسماك، كوكس بازار)، ومسؤولي المنظمات غير الحكومية المرتبطين بمشروع أبحاث الأعشاب البحرية، والشركة المصنعة المحلية لمنتجات الأعشاب البحرية، وجامعي الأعشاب البحرية، والمجتمع القبلي Mog أو Rakhyine في كوكس بازار وجزيرة سانت مارتن. يتسبب الافتقار إلى المعرفة بشأن التوافر والتوزيع والتغير الموسمي وحالة الاستخدام في إعاقة الاستخدام (مثل الأعشاب البحرية كغذاء بشري، والغرويات المائية، والأعلاف الحيوانية، والأسمدة، ومنتجات مستحضرات التجميل، وما إلى ذلك) للأعشاب البحرية المتاحة التي توجد بشكل طبيعي في بنغلاديش. تتوفر الأعشاب البحرية على طول الساحل البنغلاديشي بأكمله، معظمها في جزيرة سانت مارتن وغابة كوكس بازار وسونداربانز مانغروف. تم العثور على ما مجموعه 193 نوعًا من الأعشاب البحرية بما في ذلك 19 نوعًا مهمًا تجاريًا، تنتمي إلى 94 جنسًا. يتوفر ما يقرب من 5000 طن متري من الكتلة الحيوية للأعشاب البحرية. بسبب ...